The making of economic policy : history, theory, politics - Sheffrin, Steven M. (Cambridge, Mass. ; Oxford : B. Blackwell, 1989)
It depicts the important connection between financial processes and the macroeconomic environment in economic analysis. Areas of interest include stock market rationality, expectations and the business cycle debate.
Includes index.
Bibliography: p. [215]-228.
sju22/07/2019
Loans
Keywords: Economic stabilization; Business cycles; Keynesian economics; United States; United States; United States